Igneous Rock Associations 25. Pre-Pliocene Andean Magmatism in Chile - Oliveros, Veronica; Moreno-Yaeger, Pablo; Flores, Laura (Geoscience Canada, 2020)
Andean-type magmatism and the term ‘andesite’ are often used as the norm for the results of subduction of oceanic lithosphere under a continent, and the typical rock formed. Although the Andes chain occupies the whole western margin of South America, the most comprehensively studied rocks occur in the present-day Chilean territory and are the focus of this paper. Andean magmatism in this region developed from the Rhaetian-Hettangian boundary (ca. 200 Ma) to the present and represents the activity of a long-lived continental magmatic arc. This paper discusses Pre-Pleistocene volcanic, plutonic, and volcano-sedimentary rocks related to the arc that cover most of the continental mass of Chile (between the Pacific coast and the High Andes) between the latitudes of 18° and 50°S. They comprise most of the range of sub-alkaline igneous rocks, from gabbro to monzogranite and from basalt to rhyolite, but are dominated by the tonalite-granodiorite and andesite example members. Variations in the petrographic characteristics, major and trace element composition and isotopic signature of the igneous rocks can be correlated to changes in the physical parameters of the subduction zone, such as dip angle of the subducting slab, convergence rate and angle of convergence. Early Andean magmatic products (Jurassic to Early Cretaceous) are found along the Coastal Cordillera in the westernmost part of the Andes. The rock record of the subsequent stages (Late Cretaceous, Paleocene–Early Eocene, Middle Eocene–Oligocene, Miocene) is progressively shifted to the east, reflecting migration of the magmatic front towards the continent. Tectonic segmentation of the convergent margin, as attested by the magmatic record, may have occurred throughout the Andean life span but it is particularly evident from the Eocene onwards, where the evolution of the northern part of the Chilean Andes (north of 27°S latitude) is very different to that of the southern segment (south of 27°S latitude). RÉSUMÉ Le magmatisme de type andin et le terme « andésite » sont souvent les appellations utilisées pour décrire les résultats de la subduction de la lithosphère océanique sous un continent, et la roche typique formée. Bien que la chaîne des Andes occupe toute la marge ouest de l’Amérique du Sud, les roches les plus étudiées se trouvent dans le territoire chilien actuel et sont l’objet de cet article. Le magmatisme andin dans cette région s’est développé depuis la limite rhéto-hettangienne (environ 200 Ma) jusqu’à aujourd’hui et représente l’activité d’un arc magmatique continental persistant. Cet article a pour sujet les roches volcaniques, plutoniques et volcano-sédimentaires du pré-Pléistocène liées à l’arc qui couvrent la majeure partie de la masse continentale du Chili (entre la côte du Pacifique et les Hautes Andes) entre les latitudes de 18° et 50°S. Elles comprennent la majeure partie de la gamme de roches ignées sous-alcalines, du gabbro à la monzogranite et du basalte à la rhyolite, mais sont dominées par des roches de type tonalite-granodiorite et andésite. Les variations des caractéristiques pétrographiques, de la composition des éléments majeurs et traces et de la signature isotopique des roches ignées peuvent être corrélées aux changements des paramètres physiques de la zone de subduction, tels que l’angle de pendage de la plaque plongeante, le taux de convergence et l’angle de convergence. Les premiers produits magmatiques andins (du Jurassique au Crétacé inférieur) se trouvent le long de la Cordillère de la Côte dans la partie la plus occidentale des Andes. La succession de roche des stades suivants (Crétacé supérieur, Paléocène – Éocène inférieur, Éocène moyen – Oligocène, Miocène) est progressivement déplacée vers l’est, reflétant la migration du front magmatique vers le continent. La segmentation tectonique de la marge convergente, comme l’attestent les enregistrements magmatiques, peut avoir eu lieu tout au long de la formation des Andes, mais elle est particulièrement évidente à partir de l’Éocène, où l’évolution de la partie septentrionale des Andes chiliennes (au nord de 27°S de latitude) est très différente de celle du segment méridional (sud de 27°S de latitude).